Effects of polar cosolvents on cocoa butter extraction using supercritical carbon dioxide - Asep, E. K.; Jinap, Selamat; Jahurul, Md. Haque Akanda; Sarker, Md. Zaidul Islam; Singh, H. (ACS Publications, 2013)
Cocoa butter was successfully extracted from cocoa liquor by supercritical carbondi oxide (SC-CO2) at 35 MPa, 60 oC and 2 mL/min with 5%, 15% and 25% cosolvents. The extraction yield of tryglicerides (TG) and fatty acid (FA) compositions were significantly influenced by the concentration of polar cosolvents. The SC-CO2 extraction efficiency was increased with cosolvent significantly. Ethanol was found to be the best cosolvent for cocoa butter extraction using SC-CO2 followed by isopropanol and acetone. The triglycerides of POP, POS and SOS were contained in the extracted cocoa butter with POS being the major component. Where palmitic, stearic and oleic were the main fatty acids in the cocoa butter samples, with stearic being the highest component. The lower molecular weight (MW) of TGs and FAs showed the higher selectivity compared to the high MW of TGs and FAs. Thus, they were fractionated during the first stage of SC-CO2 process.